Semiotics 'Love Myself Campaign' BTS Korean Boyband (Case Study: 'Epiphany' Comeback Trailer Video) - Siti Khodijah Lestari (Wimba : Jurnal Komunikasi Visual, 2020)
'Epiphany' comeback trailer is one of the opening music videos in the Love Yourself: Answer album sung and played by Jin, the oldest member of BTS. This video is a representation of the Love Myself campaign message promoted by BTS with Unicef Korea in 2018. Then, the analysis focuses on the mirrored scene in Epiphany's music video which is shown repeatedly three times compared to other scenes. This study uses a qualitative approach, with text analysis using Roland Barthes' semiotics by looking at the denotation, connotation and myth. In addition, data collection by non-participant observation, literature study and documentation. The results of this study indicate that the message of the Love Myself campaign in the Epiphany music video is a reflection of what is happening in the community. When someone tries to look good but if it is done solely for the sake of others it will make oneself miserable. Before someone strives for something for someone else, it is better to put yourself first by loving yourself.